STUDENTS’ DIFFICULTIES IN TRANSLATING RECOUNT TEXT FROM INDONESIAN INTO ENGLISH AT GRADE XI IN SMA NEGERI 3 PEMATANGSIANTAR - Ribka Angelita Siadari; Sanggam Siahaan; Bloner Sinurat (Jurnal Ilmiah Pendidikan dan Keislaman, 2025)
This study aims to investigate the difficulties experienced by Grade XI students at SMA Negeri 3 Pematangsiantar in translating recount texts from Indonesian into English. Using a descriptive qualitative method, the research focuses on one class consisting of 36 students during the 2024–2025 academic year. The students were asked to translate a recount text titled “Perjalanan ke Candi Borobudur” (A Trip to Borobudur Temple), which contains linguistic and cultural elements that pose challenges in translation. Data were collected through students’ written translations, classroom observations, and interviews. The analysis revealed four main categories of difficulties: grammatical errors, particularly in the use of the simple past tense; lexical errors due to literal translation; structural errors influenced by Indonesian syntax; and problems translating culture-specific expressions. These findings suggest that students often rely on direct translation strategies, leading to inaccurate and unnatural English output. The study highlights the importance of integrating grammar instruction, vocabulary development, and cultural awareness in translation teaching. Additionally, employing a genre-based approach can help students better understand the features and conventions of recount texts, thereby improving their translation accuracy. The results imply that targeted instructional strategies and consistent practice are essential for enhancing students’ translation competence and overall English proficiency. This study contributes to understanding the linguistic and cultural challenges in EFL translation contexts and offers practical recommendations for language educators.